How accurate are teacher and parent judgements of lower secondary school children’s test anxiety? - Karing, Constance; Dörfler, Tobias; Artelt, Cordula (Educational psychology, 2015)
This study examined teacher and mother judgement accuracy of children’s worries and emotionality in the school subjects of German and mathematics. The participants were 59 German language and 58 mathematics teachers, 572 mothers and their children at the end of Grade 6. The analyses for the total sample revealed weak-to-moderate correlations between adult’s and children’s perception of test anxiety. Moreover, we found that teachers overestimated children’s emotionality as well as children’s worry, whereas mothers underestimated children’s worry and overestimated children’s emotionality in both subjects. However, when looking at the highly test-anxious children, we found quite low correlations and an underestimation of children’s worry and emotionality in both school subjects. Thus, it seems important to provide teachers and parents with information about test anxiety and possibly training to improve their judgement accuracy because of moderating effects of test anxiety on achievement.
Published online: 30 Jul 2013
Gesehen am 12.06.2020